Change in major fatty acid composition of vegetable oil depending on phenolic incorporation and storage period - Toker, O. S.; Ozturk, I.; Karaman, S.; Yalcin, H.; Kayacıer, Ahmed; Dogan, M. (Codon Publications, 2016)
In the present study, response surface methodology was conducted for the determination of effects of some phenolics (gallic acid, ellagic acid and quercetin) on the major fatty acid composition of vegetable oil prepared by mixing of sunflower and hazelnut oil (50:50, v/v) during storage at a constant temperature (50 degrees C). In this respect, major fatty acid composition (palmitic, stearic, oleic and linoleic acid) of vegetable oil was determined. Predictive regression equations were constructed for the estimation of each studied parameter (R-2>0.735). Storage period caused a significant increase in palmitic acid, stearic acid and oleic acid content of oil while it caused a decrease in the linoleic acid content of the oil (P<0.01) because of the reactions that occurred in the structure of the oil during storage. In general, gallic acid and quercetin were found to be effective on the preservation of oil against oxidation and addition of gallic acid that retarded the change of major fatty acids composition due to oxidation. Multiple response optimisation was performed by considering the change in all major fatty acids simultaneously. According to the results, addition of ellagic acid, gallic acid and quercetin at the concentrations of 20, 46.7 and 33.3%, respectively, in a phenolic mixture (0.1 g) to the oil sample is convenient for decreasing oxidation.
YALCIN, HASAN/0000-0002-1038-1877; Toker, Omer Said/0000-0002-7304-2071; DOGAN, Mahmut/0000-0003-1639-4641; SAGDIC, OSMAN/0000-0002-2063-1462
Keywords: fatty acids; storage; multiple response optimisation; oxidation; phenolics; response surface methodology; vegetable oil